Rape of vulnerable and legal abortion - Dieguez, Roberta; Rosa, Hevelyn; Lamperti Thomazi, Guilherme; da Silva Cabral, Cristiane (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2024)
This article analyzes how the age of consent category is articulated with notions of child sexuality, modulating access to reproductive rights, especially legal abortion. Consent, defined as an individual rational act by an autonomous subject, free from constraints, has been a determining factor in the definition of lawful sexual acts in the Brazilian and international legal fields. However, rather than being a well-defined concept, consent is unstable and contradictory, varying according to the actors who evoke it and the historical and political context in which it is enunciated. In the context of child protection, the controversies over who is considered a political subject of rights based on consent stand out in the face of the hierarchical production of difference. Questions such as class, race and gender permeate these relationships, affecting the guarantee of state protection, especially in the face of restrictions on abortion.